Improvisations towards a sonorous ethics in Aotearoa New Zealand - Lowe, Sebastian J. (The Australian journal of anthropology, 2024)
Taonga puoro is a Māori instrumental tradition through which one cultivates an improvisational form of playing with the world. It does not follow musical notation. ‘Instruments’ vary from rocks, to bones, wood and other non-traditional materials, such as glass. They can be found in situ, or carefully crafted and gifted. Each performance is different, new and responsive not only to the riffing soundings of fellow humans but also to the wider worlds of more-than-human sensuous agency with which we attune, respond and participate. In both their materiality and their performativity, taonga puoro draws attention to points of convergence, in which histories, ancestors, human and more-than-human entities mingle as affective co-collaborators in a world already playing in co-composition. Thinking and riffing with this idea of co-composition as a practice of attuning to how I participate in the world that I have come to know, this sound–image–text article is made to revisit and dwell within moments of creative-critical world-making through playing with my close friend Jessica Kahukura (Te Ātihaunui-a-Pāpārangi, Ngā Rauru, Ngāti Kahungunu, Ngāti Tūwharetoa). It focuses particularly on my own practices as a Pākehā (non-Māori New Zealander) researcher-musician by attuning to my creative-critical positionality in relation to a broader politics and ethics of participation and invention.